DISTANCE EDUCATION AS AN EFFECTIVE TOOL FOR IMPROVEMENT MEDIA LITERACY OF YOUNGER SCHOOL STUDENTS - Ivanova , Lydia (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2024)
The article proves that skillfully organized distance learning directly affects the media literacy of a junior high school student, which in turn helps the effective organization of online learning; the main aspects of distance learning that influence the improvement of media literacy in primary school lessons are highlighted; the conditions for the organization of online education, which will ensure the formation of media knowledge as much as possible, have been clarified.